Identifying Management Concepts in Improving the Quality of Islamic Education in Indonesia - Hidayah, Nur; Murtafiah, Nurul Hidayati (Bulletin of Science Education, 2023)
Initially, education management in Indonesia still had a lot to do with updating to keep up with the times. This is what causes the many changes that always occur in the education system in Indonesia, including Islamic education. This research aims to identify management concepts in improving the quality of Islamic education in Indonesia. The research method used is literature study (library research), namely taking data from various literature that is related to the topic being discussed. The discussion method used is a descriptive-analytical method, which explains and combines the main ideas which are of course related to the topic being discussed. The results of the research show that there are several factors related to the management of Islamic education that influence the quality of education in it, including the resources that must be adequate, appropriate facilities and infrastructure and the management of education itself which must be regulated to maximize Islamic education in Indonesia. Not only that, there are also many processes and principles that must be understood by every management in Islamic education in order to adapt it to the goals of education itself. Keywords: Management Concepts, Quality of Islamic Education, Improving Quality Education